Clinical study of renal artery cold perfusion combined with laparoscopic nephron retention in the treatment of complex renal angiomyolipoma - Zhu, ChaoShuai; Yin, HuaQi; Zhao, ShiMing; Ma, YongKang; Sun, ZhengHui; Zhu, MingKai; Du, Zheng; Yang, Tiejun (Frontiers in Oncology, 2023)
Objective: To summarize the surgical experience of renal artery cold perfusion combined with laparoscopic nephron preserving surgery for the treatment of complex renal angiomyolipoma, and to evaluate the safety and feasibility of this surgical protocol.Materials and methods: Clinical data of 9 patients who received renal artery cold perfusion combined with laparoscopic nephron preserving surgery for complex renal angiomyolipoma in our hospital from February 2017 to August 2020 were retrospectively analyzed. The study parameters included imaging findings, total renal function before and after surgery, GFR of affected kidney before and after surgery and related complications.Results: 8 of the 9 patients successfully completed the operation, 1 patient was intolerant to renal artery balloon implantation, the success rate of the operation was 88.89%.The mean maximum tumor diameter was 6.8cm and RENAL score was 7 points.Postoperative total renal function and GFR of the affected kidney had no significant changes compared with that before surgery, and imaging examination showed no tumor residue or recurrence Conclusion: This surgical procedure is safe and feasible for complex renal angiomyolipoma, and can be used as a surgical option for renal hamartoma. The long-term effect needs to be confirmed by further studies.